Taxonomic profiling of bacterial community structure from coastal sediment of Alang–Sosiya shipbreaking yard near Bhavnagar, India. Issue 2 (30th December 2015) - Patel, Vilas; Munot, Hitendra; Shah, Varun; Shouche, Yogesh S.; Madamwar, Datta
Abstract: The Alang–Sosiya shipbreaking yard (ASSBY) is considered the largest of its kind in the world, and a major source of anthropogenic pollutants. The aim of this study was to investigate the impact of shipbreaking activities on the bacterial community structure with a combination of culture-dependent and culture-independent approaches. In the culture-dependent approach, 200 bacterial cultures were isolated and analyzed by molecular fingerprinting and 16S ribosomal RNA (r-RNA) gene sequencing, as well as being studied for degradation of polycyclic aromatic hydrocarbons (PAHs). In the culture-independent approach, operational taxonomic units (OTUs) were related to eight major phyla, of which Betaproteobacteria (especially Acidovorax ) was predominantly found in the polluted sediments of ASSBY and Gammaproteobacteria in the pristine sediment sample. The statistical approaches showed a significant difference in the bacterial community structure between the pristine and polluted sediments. To the best of our knowledge, this is the first study investigating the effect of shipbreaking activity on the bacterial community structure of the coastal sediment at ASSBY. Highlights: Shipbreaking activities increase the level of anthropogenic pollutants in the coastal sediment. The structure of the bacterial community shifts from Gammaproteobacteria to Betaproteobacteria. Acidovorax sp. was found to be a potential indicator of metal and other anthropogenic pollutants.